Completion of the Consonant Inventory of Arabic. - Amayreh, Mousa M. (Journal of Speech, Language & Hearing Research, 2003)
This study is a follow-up of previous research on the acquisition of Arabic consonants in normally developing children between the ages of 2 and 6 years. The purpose of this study was to pr9vide normative data on the acquisition of late consonants that had not been acquired by the age of 6;4 (years;months). Speech samples from 60 Arabic-speaking children between ages 6;6 and 8;4, in Amman, Jordan, were analyzed to determine the age at which 10 late consonants had been acquired and to determine the error patterns and sound changes used. Five of these consonants had still not been acquired in their standard form (Educated Spoken Arabic) by even the oldest children. However, 8 of the late consonants were produced in their acceptable colloquial forms by age 7;4 and all 10 by age 8;4. The late acquisition of these consonants was discussed from the point of view of functional load and markedness. Implications for diagnosis of articulation disorders and reading problems were considered. Reprinted by permission of the publisher.